Lethal Zika Virus Disease Models in Young and Older Interferon α/β Receptor Knock Out Mice - Marzi, Andrea; Emanuel, Jackson; Callison, Julie; McNally, Kristin L.; Arndt, Nicolette; Chadinha, Spencer; Martellaro, Cynthia; Rosenke, Rebecca; Scott, Dana P.; Safronetz, David; Whitehead, Stephen S.; Best, Sonja M.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
The common small animal disease models for Zika virus (ZIKV) are mice lacking the interferon responses, but infection of interferon receptor α/β knock out (IFNAR-/-) mice is not uniformly lethal particularly in older animals. Here we sought to advance this model in regard to lethality for future countermeasure efficacy testing against more recent ZIKV strains from the Asian lineage, preferably the American sublineage. We first infected IFNAR-/- mice subcutaneously with the contemporary ZIKV-Paraiba strain resulting in predominantly neurological disease with 50% lethality. Infection with ZIKV-Paraiba by different routes established a uniformly lethal model only in young mice (4-weeks old) upon intraperitoneal infection. However, intraperitoneal inoculation of ZIKV-French Polynesia resulted in uniform lethality in older IFNAR-/- mice (10-12-weeks old). In conclusion, we have established uniformly lethal mouse disease models for efficacy testing of antivirals and vaccines against recent ZIKV strains representing the Asian lineage.